Water-Erodible Xanthan-Acrylate-Polyurethane Antifouling Coating - Rahman, Mohammad Mizanur (Polymers (Basel), 2019)
Biopolymer xanthan (Xn) and its functionalized polymer xanthan acrylate (XnAc) were used to improve the antifouling properties of synthesized waterborne polyurethane (WBPU) coatings, namely, WBPU-Xn and WBPU-XnAc. XnAc was synthesized by functionalization of xanthan (Xn) using polyacrylic acid. Coating hydrophilicity, adhesive strength, and erosion all varied with the Xn and XnAc contents. A moderate erosion rate was recorded only for the WBPU-XnAc coating. A good antifouling property for longer time was found in the WBPU-XnAc coating using zinc pyrithione as a biocide in the field test.